Temporal trends of arrhythmias at delivery hospitalizations in the United States: Analysis from the National Inpatient Sample, 2009–2019 - Thakkar, Aarti; Kwapong, Yaa A.; Patel, Harsh; Minhas, Anum S.; Vaught, Arthur J.; Gavin, Nicole; Zakaria, Sammy; Blumenthal, Roger S.; Wu, Katherine C.; Chrispin, Jonathan; Dani, Sourbha S.; Sharma, Garima (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac arrhythmias are associated with increased maternal morbidity. There are limited data on trends of arrhythmias among women hospitalized for delivery. Methods: We used the National Inpatient Sample database to identify delivery hospitalizations for individuals aged 18-49 years between 2009 to 2019 and utilized coding data from the 9th and 10th editions of the International Classification of Diseases to identify supraventricular tachycardias (SVT), atrial fibrillation (AF), atrial flutter, ventricular tachycardia (VT), and ventricular fibrillation (VF). Arrhythmia trends were analyzed by age, race-ethnicity, hospital setting, and hospital geographic regions. Multivariable logistic regression was used to evaluate the association of demographic, clinical, and socioeconomic characteristics with arrhythmias. Results: Among 41,576,442 delivery hospitalizations, the most common arrhythmia was SVT (53%), followed by AF (31%) and VT (13%). The prevalence of arrhythmia among delivery hospitalizations increased between 2009 and 2019. Age > 35 years and Black race were associated with a higher arrhythmia burden. Factors associated with an increased risk of arrhythmias included valvular disease (OR: 12.77; 95% C1:1.98-13.61), heart failure (OR:7.13; 95% CI: 6.49 -7.83), prior myocardial infarction (OR: 5.41, 95% CI: 4.01-7.30), peripheral vascular disease (OR: 3.19, 95% CI: 2.51-4.06), hypertension (OR: 2.18; 95% CI: 2.07-2.28), and obesity (OR 1.69; 95% CI: 1.63-1.76). Delivery hospitalizations complicated by arrhythmias compared with those with no arrhythmias had a higher proportion of all-cause in-hospital mortality (0.95% vs 0.01%), cardiogenic shock (0.48% vs 0,00%), preeclampsia (6.96% vs 3.58%) and preterm labor (2.95% vs 2.41%)(all p<0.0001). Conclusions: Pregnant individuals with age > 35 years, obesity, hypertension, valvular heart disease, or severe pulmonary disease are more likely to have an arrhythmia history or an arrhythmia during a delivery hospitalization. Delivery hospitalizations with a history of arrhythmia are more likely to be complicated by all-cause in-hospital mortality, cardiovascular, and adverse pregnancy outcomes. These data highlight the increased risk associated with pregnancies among individuals with arrhythmias.